Outcome of delayed versus immediate casting on spasticity of lower limb muscles in cerebral palsy post-botulinum toxin injection - Suraj Kumar Choudhary K,; Naveen Babu T,; Susmith K,; Naveen Kumar P,; Jagadesh G, (Asian Journal of Medical Sciences, 2024)
Background: Botulinum toxin type A (BTX-A) is widely used to treat spasticity in children. The optimal strategy for the combined treatment of casting and BTX-A injections is not known. This prospective study is conducted to know the functional outcome of immediate versus delayed casting post-BTX-A injection in children with cerebral palsy (CP). Aims and Objectives: The aim of this study is to compare delayed versus immediate casting as an adjunct to botulinum toxin therapy for spasticity of lower limb muscles in CP. The objectives of the study are to test the hypothesis that delayed casting is superior to immediate casting post-botulinum toxin injection and to know the feasibility of using the Edinburgh visual gait score (EVGS) as a single qualitative and quantitative outcome measure. Materials and Methods: A prospective study is conducted to compare immediate casting with delayed casting post-botulinum toxin injection to spastic lower limb muscles in patients with CP from July 2018 to February 2019. Inclusion criteria: A diagnosis of CP with associated spastic monoplegia, diplegia, or hemiplegia with aided or unaided ambulation. Exclusion criteria: History of orthopedic surgery in the preceding 12 months; selective dorsal rhizotomy; mixed CP; ataxia; athetosis; non-ambulatory subjects. Results: The botulinum toxin injection + delayed POP casting group fared better in terms of clinical and functional outcome (as shown by improved EVGS scores) in our study. Conclusion: There is a clear benefit in delaying casting after the injection of Botulinum toxin in the recurrence of spasticity.